Influenza A Virus H7 nanobody recognizes a conserved immunodominant epitope on hemagglutinin head and confers heterosubtypic protection - Zhao-Shan Chen; Hsiang-Chi Huang; Xiangkun Wang; Karin Schön; Yane Jia; Michael Lebens; Danica F. Besavilla; Janarthan R. Murti; Yanhong Ji; Aishe A. Sarshad; Guohua Deng; Qiyun Zhu; et al. (Nature Communications, 2025)
Abstract Influenza remains a persistent global health challenge, largely due to the virus’ continuous antigenic drift and occasional shift, which impede the development of a universal vaccine. To address this, the identification of broadly neutralizing antibodies and their epitopes is crucial. Nanobodies, with their unique characteristics and binding capacity, offer a promising avenue to identify such epitopes. Here, we isolate and purify a hemagglutinin (HA)-specific nanobody that recognizes an H7 subtype of influenza A virus. The nanobody, named E10, exhibits broad-spectrum binding, cross-group neutralization and in vivo protection across various influenza A subtypes. Through phage display and in vitro characterization, we demonstrate that E10 specifically targets an epitope on HA head which is part of the conserved lateral patch and is highly immunodominant upon H7 infection. Importantly, immunization with a peptide including the E10 epitope elicits cross-reactive antibodies and mediates partial protection from lethal viral challenge. Our data highlights the potential of E10 and its associated epitope as a candidate for future influenza prevention strategies.